Anti-inflammatory effect of dialysable leucocyte extract in a rat model of osteoarthritis: histopathological and molecular characterization. (1st November 2016) - Acosta, P; Pérez, N; Pérez, E; Correa, B; Pérez, C; Gómez, C; Sánchez, V; Pérez, DG
Abstract : Objectives : To evaluate the effect of dialysable leucocyte extract (DLE) on pro- and anti-inflammatory profiles in a rat model of osteoarthritis (OA). Method : Forty-eight male Wistar rats were divided into three groups: normal rats without treatment, OA rats treated with placebo, and OA rats treated with DLE. After treatment, the animals were killed to obtain cartilage for histological analysis and to determine the expression of pro- and anti-inflammatory cytokines by reverse transcription multiplex polymerase chain reaction (RT-MPCR) and immunohistofluorescence analyses. Results : Histological analysis revealed that OA cartilage from rats treated with DLE displayed similar characteristics to non-OA cartilage from the control group. The OA cartilage treated with placebo showed alterations in the cellular architecture and in chondrocyte cluster formation. Analysis of cytokine expression by RT-MPCR showed that OA cartilage from DLE-treated rats expressed platelet-derived growth factor (PDGF), interferon (IFN)-γ, and fibroblast growth factor (FGF)-2, similar to non-OA cartilage from the control group. However, OA cartilage from rats treated with placebo expressed interleukin (IL)-1, PDGF, and I kappa B (IκB). Confocal immunodetection of FGF-2, PDGF, and non-phosphorylated IκB showed that they were distributed in the cytoplasm of most chondrocytes in OA cartilage from DLE-treated rats whereas no nuclear factor kappa B (NF-κB) expression was observed in the nuclei. Instead, in OA cartilage from the placebo group, only weak FGF-2 staining was observed, PDGF and IκB were not detected, and NF-κB was strongly observed in both cytoplasm and nuclei. Conclusions : Our findings suggest that DLE treatment modifies the OA process, promoting the expression of anti-inflammatory cytokines and diminishing the inflammatory effects, avoiding the nuclear translocation of NF-κB in chondrocytes.